Nutzungsabfolgen an Einzelhandelsstandorten in Geschäftsgebieten unterschiedlicher Wertigkeit - Heinritz, Günter (ERDKUNDE, 1991)
The spatial consequences of the structural change in trade are undoubtedly a highly topical subject for geographers, as dealing with it seems only reasonable with spatial differentiation. This paper analyses 3602 retail shop locations of differing centrality in the Munich area and northern Upper Bavaria, which were observed between 1981 and 1986, and particularly with those 485 locations where shops disappeared during the observation period. There was a total of1686 retail shop disappearances, 727 of which we had registered at the beginning of the project, but in only half of these cases was the location given up along with the closure of the business. Those locations of shops which already existed in 1981 clearly proved to be more worthwhile than new locations, where retail shops were opened after 1981, but 21 % of which failed. The paper demonstrates how the locations which were given up by retail trade are spread over the test areas and what their successive use is. As for the features of the area which contribute to a location's entire loss of its retailing function, the data show that the number of opportunities for customers to combine different activities in one trip (e.g. other shops and service industries), proved to have a strong influence on the persistence of shops and shop.